INVESTIGATION OF BIOKINETIC PECULIARITIES OF STRONTIUM-90 METABOLISM MODEL AND POSSIBILITY OF AN ESTIMATION OF RADIONUCLIDE INTAKE LEVEL BASING ON THE RESULTS OF THE MEASUREMENTS OF ACTIVITY IN URINE - V. S. Repin (Радиационная гигиена)
An article presents the results of the substantiation of possibility of the use of age-dependent biokinetic model of 90Sr in a human body for estimation of the average levels of a daily intake with a diet by means of measurements of radionuclide activity in a daily urine sample. It is shown that for persons of different age groups in a case of chronic intake of 90Sr the rate of excretion with urine, basically, reflect by the temporary depots of radionuclide fixation in soft tissues and on a surface of the bone, and depends slightly on accumulation of radionuclide in the whole skeleton. Besides, temporary depots of radionuclide fixation fulfill the function of averaging of radionuclide intake in a case of daily intake levels, randomly timely distributed.